Does Native Hawaiian culture-based treatment deserve more funding than treatment-as-usual?. Issue 2 (3rd April 2019) - Williams, Izaak L.
ABSTRACT: Native Hawaiian culture-based addiction treatment programs are disproportionately funded by federal entitlements exempt from treatment-as-usual and receive almost double the amount of funding designated for Native Hawaiian programs at the state level. Although substance use disorder treatment-as-usual is not grounded in Native Hawaiian cultural practices, it may nonetheless demonstrate both cultural relevancy and ethnocultural respect, and deliver increased community impact in decreasing Native Hawaiian substance use. This commentary-based narrative review, as conceptually framed, draws on the research-praxis literature involving the topic of Native Hawaiian addiction treatment. The core aim of this article is to seek evidentiary support and empirical justification for the funding disparity.